PENGARUH BRAND SIMILIARITY, BRAND REPUTATION, BRAND PERCEIVED QUALITY, DAN BRAND INNOVATION TERHADAP BRAND IMAGE PERMEN RELAXA DI KABUPATEN KENDAL - Diva Riza Fahlefi; Ariyani Indriastuti; Jefri Heridiasyah (JURNAL STIE SEMARANG, 2020)
Brand is one of the most important things in business competition. A positive brand image can increase customer loyalty to a product, including candy. The candy industry is a very competitive industry with intense competition because there are many choices of candy brands on the market. The purpose of this research is to describe whether there is influence of brand similiarity, brand reputation, brand perceived quality and brand innovation on the brand image of Relaxa candy in Kendal Regency. The population in this study was Relaxa candy in Kendal Regency numbering 477 consumers. The sample in this study was Relaxa Candy in Kendal District. The sampling technique used is purposive sampling, which is determining the sample of all populations with certain criteria. The results of this study indicate that first, brand similiarity has a positive and significant influence on the brand image of Relaxa candy in Kendal Regency. This is indicated by the largest regression coefficient of 0.214. As for the value of tcount 2.134> table (1.66) and sign 0.003. Second, brand image also has a positive effect with a regression coefficient of 0.168. As for the value of tcount 3.259> 1.66 table and 0.002 sign. Third, brand perceived quality has a significant effect on Relaxa candy brand image with a regression coefficient of 0.205. As for the value of tcount 4.669> t table 1.66 and sign 0.000. Fourth, brand innovation has a significant influence on the brand image of Relaxa candy in Kendal Regency with a regression coefficient of 0.236. As for the value of tcount 4.378> 1.66 table and 0.000 sign. In conclusion, brand similiarity, brand reputation, brand perceived quality and brand innovation have a positive and significant effect on the brand image of Relaxa candy in Kendal Regency. This is indicated by the value of Fcount 38.382> F table 2.70 with a significance value of 0.000